Straatsma Syndrome: Should Visual Prognostic Factors Be Taken into Account? A Case Report - (:unkn) unknown (My University, 2021)
Straatsma syndrome is the triad of myelinated retinal nerve fibers, myopia, and amblyopia and may be associated with strabismus, nystagmus, hypoplastic optic nerve, and heterochromia iridum. The degree of anisometropia, presence of strabismus, extent of myelination, and macular involvement have been reported to be associated with poor visual acuity after occlusion therapy for amblyopia in this syndrome. Here we present two cases of Straatsma syndrome with different responses to occlusion therapy and discuss their treatment responses according to prognostic factors for post-occlusion visual acuity.
Keywords: Amblyopia; myelinated retinal nerve fibers; prognostic factors; straatsma syndrome